The vulnerability of personal data and the ethical challenges of the information professional: a Brazilian perspective - Bagatini, Jose Augusto [UNESP]; Chaves Guimaraes, Jose Augusto [UNESP] (Ibersid Network, 2019)
The challenges and ethical role of the information professional (notably the archivist, record manager and librarian) is discussed to ensure the protection of personal data and to prevent harm to the citizen and the society. The citizen, with the daily use of computerized solutions, began to create a greater amount of traces of their behaviors, which can be interpreted as personal data as they refer directly to their actions and reveal its physical or personality characteristics. Nowadays, these data can be considered as a special kind of commodity at the surveillance market. However, there is still no discussion in Brazil that allows us to situate personal data in a more systematic way as something that is vulnerable to invasive or fraudulent actions.
Keywords: Personal data; Information ethics; Digital surveillance; Data breachs; Brasil